Pengaruh Usability, Information dan Service Interaction terhadap Minat Beli pada muslimarket.com - Rodame Monitorir Napitupulu (Jurnal Iqtisaduna, 2019)
Internet has changed the way consumer buying products. They now buy products through website. Muslimarket.com is one of the most complete e-commerce for Muslim product in Indonesia. The tight competition of e-commerce demanding muslimarket.com to optimized website as its e-marketing in order to improve buying interest so that the sharia business can also able to increase. The aim of this research is to know effect of usability, information and service interaction to buying intense through website. This research use quantitative approach. The three independent variables (usability, information and service interaction) built based on Webqual 4.0. The sample is 100 respondents that spread all over Indonesia. Based on the multiple linear regression, all independent variable: usability, information and service interaction have significant positive effect on buying interest at muslimarket.com. But partially, only information has not significant positive effect on buying interest at muslimarket.com.